2016
DOI: 10.4103/0975-1475.195113
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of sexual dimorphism using digital orthopantomographs in South Indians

Abstract: Introduction:The identification of human skeletal remains plays a crucial role in forensic investigation and its accuracy depends on the available parts of the skeleton. The mandible is the hardest and strongest bone of the skull, which exhibits a high degree of sexual dimorphism and helps to identify the sex in human remains. The aim of this study was to develop discriminant function to determine sex from the mandibular radiographs in a South Indian (Visakhapatnam) population.Materials and Methods:This retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
1
9
2
Order By: Relevance
“…In the present study, the height of coronoid, as in the studies by Sairam and Damera, had sexual dimorphism, and the ramus height in these three studies showed the highest sexual dimorphism. However, in the Sambhana study, the height of the coronoid was the most significant parameter with sexual dimorphism [1,6,12].…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…In the present study, the height of coronoid, as in the studies by Sairam and Damera, had sexual dimorphism, and the ramus height in these three studies showed the highest sexual dimorphism. However, in the Sambhana study, the height of the coronoid was the most significant parameter with sexual dimorphism [1,6,12].…”
Section: Discussionmentioning
confidence: 80%
“…Sambhana also provided an equation with an accuracy of 75.8% by examination of 10 parameters [12]. Sairam by examining 7 parameters and Indira by examining 5 parameters also obtained equations with an accuracy of 79.5% and 76%, respectively [4,6].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations